Tracking sources of PM10 emissions and deposition in the industrial city of Ostrava, Czech Republic: A carbonaceous δ13C-based approach. (15th February 2023) - Buzek, Frantisek; Cejkova, Bohuslava; Jackova, Ivana; Seibert, Radim; Curik, Jan; Veselovsky, Frantisek; Petrash, Daniel A.
Abstract: The sources of airborne particulate matter (PM10 ) emissions in Ostrava, Czech Republic, were investigated. Emphasis was placed on their organic carbon (OC) and elemental carbon (EC) contents, and their carbon stable isotope composition, δ 13 C. Emission sources were identified using OC- δ 13 C and concentration values. To track the extent of long-term deposition, these sources were also identified using the black carbon (BC) δ 13 C values of soil samples. At all sampling sites, wind flow is predominantly (65–80%) bidirectional in either SW-NE or NE-SW trajectories. Source apportionment along these dominant airflow trajectories was calculated from an isotopic 13 C mass balance, and according to differences in the OC content and δ 13 C values of PM10 . Determined emission sources are: (i) combustion of Silesian hard coal (δ 13 C = −24.5‰); (ii) local Ostrava coal combustion ( δ 13 C = −25.5 to −26‰), automotive emissions ( δ 13 C = −26.5‰), and biogenic particles ( δ 13 C = −28 to −28.5‰). Winter emissions (mean OC concentrations from 12 to 25 μg m −3 ) originated mostly from coal combustion (80%) in domestic and industrial point sources. Differences were ascribed to automotive emissions. Ostrava is located near the Czech-Polish border, transboundary emissions are transported under a southbound wind flow that transported from 40 to 80% of the collected PM10 . Summer emissions were lower (mean OC concentration from 6 to 8 μg m −3 ). Automotive emissions accounted for up to 40%, whilst biogenic production accounted for 60%. Absence of 13 C isotope data of secondary OC (SOC 1.2–1.5 μg m −3 ) increases uncertainty in our source apportionment in summer; when SOC could comprise >20% of total OC. Contribution of SOC to the winter-measured OC is much lower (5–10%), and has no significant effect on mass balances. The upper soil layer analyses revealed long-term deposition of the same emissions sources. We conclude that the stable δ 13 C isotope values of OC and EC are useful for discriminating against local sources of PM10 pollution in relatively small urban areas, containing discrete polluting sources. Such a simplified approach can be easily standardized and implemented to manage regulatory compliances in the increasingly commoditized carbon offset market. Graphical abstract: Apportionment of sources of PM emissions in Ostrava area represented by the OC concentration under northern wind conditions. The sampled sites are presented on the x axis, and the OC concentrations are on the y axis. Apportionment of OC sources in PM10 emissions in Ostrava 2021 at S wind conditions Image 1 Highlights: Sources of particulate matter emissions were traced using 13 C data of organic and black carbon. Studied area is the industrial city area with numerous pollution sources. The apportionment of sources was calculated from the mass balance of organic carbon and 13 C. Deposition of emissions was detected in 13 C of black carbon on surface layer of soils.